The effects of competence, independence, audit work, and communication on the effectiveness of internal audit - Dyah Setyaningrum; Cris Kuntadi (Universitas Hayam Wuruk Perbanas, 2019)
The purpose of this study was to examine the effect of competence, independence, audit work and communication on internal audit effectiveness. This research is still relevant due to lacking in internal audit function as there are still many corruption cases, especially in the Ministries/Agencies. This is a quantitative research using questionnaires distributed to the auditors in Inspectorate General of the Ministry of Transportation as respondents.Â Inspectorate General of the Ministry of Transportation is one of the institutions with IACM level 3 (integrated) in Indonesia. It showed that competence, communication, and audit work have positive effect on internal audit effectiveness, while independence has no effect on internal audit effectiveness. It implies that the auditors should be equipped with the audit technical competence as well as non-technical competencies relevant with their audit area. Audit work from planning, implementation and post-audit should always comply with audit standard. Effective oral and written communication between the auditor and the auditee should also be enhanced in form of audit reports to the follow-up of audit recommendations. Independence in this study does not affect the effectiveness of the internal audit, because independence is fact is main requirement when conducting audit.